Mapping Green Financial Management Research Trends with a Global Bibliometric Study - Judijanto, Loso; Qosim, Nanang; Regar, Erfendi; Arifin, Hasmia Melati; Faisal, Muhammad (The Eastasouth Management and Business, 2025)
This bibliometric study analyzes the dynamic landscape of green finance research from 2000 to 2023, revealing the evolution of key themes, geographic and collaboration patterns, and shifts in research focus over time. Utilizing data from Scopus and VOSviewer, the study highlights significant growth in publications, particularly post-2015, aligned with increased global attention towards sustainable development. The research maps out central themes including "green bonds," "sustainable development," and "climate finance," and identifies China as a predominant contributor, reflecting its strategic initiatives towards environmental sustainability. Collaboration networks indicate robust partnerships within and across regions, particularly Asia and Europe, emphasizing the global scope of green finance. The study discusses challenges like standardization and greenwashing and suggests future directions including the integration of technology in green finance. This comprehensive overview provides valuable insights into the trends and transformations within green finance research, highlighting its increasing importance in achieving global sustainability goals.